Pembiayaan Program Perbaikan Gizi Masyarakat terhadap Capaian Kinerja - Dwi Noerjoedianto; Fitria Eka Putri; Andy Amir; Andi Subandi (Journal of Telenursing (JOTING), 2021)
This study aims to assess and find out how to finance community nutrition improvement programs on the performance achievements of the nutrition program at Sengeti Public Health Center. This type of research is qualitative research. Data sources were obtained from primary data with in-depth interviews and secondary data by reviewing documents and documentation. Data collection was carried out at the Sengeti Community Health Center, Muaro Jambi Regency. Data analysis through content analysis with triangulation. The results showed that: 1) the proportion of funding for the nutrition program was classified as adequate; 2) the roles and efforts of the nutrition management team always coordinate both in quantity and quality following the existing Minimum Service Standards (SPM) in nutrition management; 3) the performance achievements are following the established indicators. In conclusion, the proportion of the nutrition program budget is classified as sufficient. The person's role and efforts in charge of the nutrition program are good thanks to the support of related stakeholders to achieve performance according to the SPM indicators and determined targets. Keywords: Nutrition Program Achievement Indicators, Team Roles and Tasks, Nutrition Financing Program, Budget Proportion